Bioavailability of dietary polyphenols: Factors contributing to their clinical application in CNS diseases. (October 2015) - Pandareesh, M.D.; Mythri, R.B.; Srinivas Bharath, M.M.
Abstract: The anatomical location of the central nervous system (CNS) renders it immunologically and pharmacologically privileged due to the blood brain barrier (BBB). Although this limits the transport of unfavorable molecules to the CNS, the ensuing privilege could be disadvantageous for therapeutic compounds. Hence, the greatest challenge in the pharmacotherapy of CNS diseases is to ensure efficient brain targeting and drug delivery. Research evidences indicate that dietary polyphenols have neuroprotective potential against CNS diseases. However, their selective permeability across BBB, poor absorption, rapid metabolism and systemic elimination limit their bioavailability and therapeutic efficacy. Consequently, the beneficial effects of these orally administered agents in the CNS still remain a subject of debate. This has also limited its clinical application either as independent or adjunctive therapy. Improving the in vivo bioavailability by novel methods could improve the therapeutic feasibility of polyphenols and assist in evolving novel drugs and their derivatives with improved efficacy in vivo . Here we review the mechanistic and pharmacological issues related to the bioavailability of polyphenols with therapeutic implications for CNS diseases. We surmise that improving the bioavailability of polyphenols entails efficient in vivo transport across BBB, biochemical stability, improved half-life and persistent neuroprotection in the CNS.